Optimizaton of Cationic Lipid Mediated Transfection of pEGFP-c1 and pJ-EPO Plasmids in Chinese Hamster Ovary (CHO) Cells Attached Culture for Transient and Stable Recombinant Human Erythropoietin (rhEPO) Expression - Septisetyani, Endah Puji; Kusumawati, Arizah; Santoso, Adi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2015)
Cationic lipid is one of transfection agents which show high efficiency and low cytotoxicity. The transfection efficiencies may depend upon the type or amount of cationic lipids, the cell line or DNA plasmid being used for transfection. The purpose of this study was to find optimal condition for transfection of CHO-K1 and CHO-S cells with pJ-EPO plasmid (contain human epo gene) compared with pEGFP-c1 plasmid (contain gfp gene) by cationic lipid Lipofectamin 2000TM to generate stable transfectant expressing recombinant human erythropoietin (rhEPO). Optimization was carried out regarding the amount of lipofectamin, DNA concentration, and concentration of antibiotic Geneticin (G418) for selection of stable transfectants. Using standard amount of lipofectamin (10µl/well) in 6-well plate, highest expression level of green fluorescent protein (GFP) was shown after transfection of CHO-K1 cells with 4µg/well pEGFP-c1 while highest expression level of rhEPO was observed after transfection of CHO-K1 cells with 6, 8, and 10µg/well pJ-EPO plasmids. The data also indicated that optimal transfection conditions of CHO-K1 and CHO-S cells with pJ-EPO were shown with the use of 4µg/well DNA and 15µl lipofectamin, respectively. Concentration of G418 affected the expression where strongest rhEPO expression was shown at 1,000 ng/µl G418 concentration.